1022. COLCHICUM MACROPHYLLUM: Colchicaceae. (11th June 2022) - Rix, Martyn; Wilford, Richard; King, Christabel
Summary: Colchicum macrophyllum B.L. Burtt, is illustrated. Its distribution in the eastern Mediterranean is discussed. It has the largest leaves of all the species of Colchicum .